Reviewing the Role of Investment in the West Kalimantan Border - Dian Anggraeny Rahim (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
The development of border areas that is rampantly carried out by the government, in addition to reducing regional disparities, also improves regional economic performance as one of the efforts made by the government is through PMA (foreign direct investment) and PMDN (domestic investment). Furthermore, the role of this investment is evaluated to see the extent of its success in the area's economic performance. The study had two objectives; first, to know what variables affect the reduction of the poverty rate and increase in GDP per capita in the border area of West Kalimantan covering five districts, namely Sambas, Bengkayang, Sanggau, Sintang, and Kapuas Hulu. The independent variables used in this study are the realization of PMA and PMDN investment, the number of industries, and the absorption of labor in the industrial sector. Using secondary data for 2019-2021 and Panel Data Regression analysis, it can be seen that only employment in the industrial sector influences increasing GDP per capita and decreasing poverty rates. Meanwhile, the realization of PMA and PMDN investment, as well as the number of industries, did not significantly influence. The second objective of this study is to determine which investment is better based on the Forecasting Method. The Naive Method shows that PMDN investments have a smaller MSE value and a lower MAPE value than PMA investments. It means that PMDN investment is more feasible to be used as an option for future funding development in border areas.